Can a bronchoscopist reliably assess a patient's experience of bronchoscopy? - Hadzri, HM (Royal Society of Medicine Press, 2010)
OBJECTIVES: Bronchoscopy is an essential investigative tool in many respiratory complaints. The procedure can be unpleasant for both bronchoscopists and patients. To the best of our knowledge, there are only a few studies that correlate the bronchoscopist's satisfaction with that of the patient's during bronchoscopy. The aim of our study is to assess whether or not a bronchoscopist could reliably assess a patient's satisfaction during bronchoscopy. DESIGN: Cross-sectional, observational study with convenience sampling. SETTING: Patients attending flexible fibreoptic bronchoscopy appointments at the bronchoscopy suite, Respiratory Unit, Universiti Kebangsaan Malaysia Medical Centre (UKMMC), Cheras, Kuala Lumpur, Malaysia between March and September 2006. PARTICIPANTS: Sixty patients undergoing bronchoscopy over a 6-month period completed a questionnaire after the procedure. All patients received standard pre-medication with intravenous midazolam. MAIN OUTCOME MEASURES: Bronchoscopists and patients rated the level of satisfaction of the procedure using a 10 cm visual analogue scale (VAS). Lower scores indicated better satisfaction or less discomfort. Patients and bronchoscopists also rated coughing, choking and vomiting perception using the same 10 cm VAS. Reliability analysis (intra-class correlation coefficient [ICC]) was used to analyse the correlation between patients' and bronchoscopists' VAS scores. RESULTS: All 60 patients answered the questionnaire. The median overall satisfaction scored by bronchoscopists was 2.2 (2.0) with a non-significant (p = 0.880) trend to a better median overall satisfaction of 1.9 (2.3) scored by patients. The VAS scores for cough sensation were 1.9 (2.7) and 1.5 (5.0), respectively. There was positive correlation between bronchoscopists' and patients' VAS scores for coughing sensation (p = 0.047, ICC = 0.233). No significant correlation for overall satisfaction, vomiting sensation and choking sensation was found. CONCLUSION: Positive correlation for cough perception suggested that the bronchoscopist could reliably assess the degree of cough discomfort patients experience during bronchoscopy.